Self-assembly of 1,3,5-benzenetribenzoic acid on Ag and Cu at the liquid/solid interface - Aitchison, Hannah; Lu, Hao; Morena, Rodrigo Ortiz de la; Cebula, Izabela; Zharnikov, Michael; Buck, Manfred (Physical chemistry, chemical physics, 2018)
Assembly of 1,3,5-benzenetribenzoic acid (H3BTB) from solution on Au substrates modified by underpotential deposited Ag and Cu layers was studied by near edge X-ray absorption fine structure spectroscopy, X-ray photoelectron spectroscopy and scanning tunneling microscopy. Adsorption of H3BTB on Cu resulted in disordered layers with sporadic occurrence of ordered molecular aggregates. In contrast, highly ordered layers were obtained on Ag which exhibit a pronounced row structure and involve a monopodal bidentate adsorption geometry of the molecules through carboxylate coordinating bonding. The row structure arises from π-stacking of the molecules and is accompanied by hydrogen bonding interactions between the COOH groups of adjacent rows. As a consequence of the geometry of the H3BTB molecule and the dominance of intermolecular over molecule-substrate interactions, the SAM forms an open structure featuring a grooved surface and nanotunnels.